Malnutrition as a risk factor for post-operative morbidity in gynecologic cancer: Analysis using a national surgical outcomes database - Goins, Emily C.; Weber, Jeremy M.; Truong, Tracy; Moss, Haley A.; Previs, Rebecca A.; Davidson, Brittany A.; Havrilesky, Laura J. (Gynecologic oncology, 2022)
To assess, using a national surgical outcomes database, the association of various malnutrition definitions with post-operative morbidity in three gynecologic malignancies. Patients undergoing resection of ovarian, uterine, or cervical cancer between 2005 and 2019 were identified using the National Surgical Quality Improvement Program (NSQIP) database. Patients were classified based on specific, pre-defined malnutrition criteria: severe malnutrition (Body Mass Index (BMI) <18.5 + 10% weight loss), European Society for Clinical Nutrition and Metabolism ((ESPEN1); BMI 18.5–22 + 10% weight loss), ESPEN2 (BMI < 18.5), American Cancer Society ((ACS); normal/overweight BMI + 10% weight loss), mild malnutrition (BMI 18.5–22), or albumin (<3.5 g/dL). Outcomes included 30-day major complications, readmission, reoperation. Modified Poisson regression estimated associations between definitions and outcomes. Of 76,290 total patients undergoing surgery, those meeting malnutrition definitions were: severe-98 (0.1%), ESPEN1–148 (0.2%), ESPEN2–877 (1.1%), ACS-1028 (1.3%), mild-2853 (3.7%), and albumin (11.1%). Complication rates were: unplanned readmission-5.5%, reoperation-1.7%, major complications-13.5%. For ovarian cancer, ESPEN2 malnutrition was associated with higher readmissions (risk ratio 1.69; 95% confidence interval 1.29–2.20), reoperations (2.53; 1.70–3.77), and complications (1.36; 1.20–1.54). For uterine cancer, ACS malnutrition was associated with readmissions (2.74; 2.09–3.59), reoperations (3.61; 2.29–5.71) and complications (3.92; 3.40–4.53). For cervical cancer, albumin<3.5 g/dL was associated with readmissions (1.48; 1.01–2.19), reoperations (2.25; 1.17–4.34), and complications (2.59; 2.11–3.17). Albumin<3.5 was associated with adverse outcomes in ovarian and uterine cancer. Preoperative risk assessments might be tailored using cancer-specific malnutrition criteria. Major complications, readmissions, and reoperations are all associated with the ESPEN2 definition for ovarian cancer, the ACS definition for uterine cancer, and with albumin<3.5 for all cancers. [Display omitted] •We used a national surgical database to study malnutrition definitions and post-surgical morbidity in gynecologic cancer.•Patients meeting malnutrition criteria were mild-3.7%, severe-0.1%, ESPEN1–0.2%, ESPEN2–1.1%, and ACS-1.3%.•In uterine cancer, weight loss and albumin were associated with major complications, reoperation, and readmission.•In cervical cancer, only albumin was associated with increased risk of all pre-designated outcomes.•In ovarian cancer, weight loss, low body mass index, and albumin were associated with post-operative adverse outcomes.